2013
DOI: 10.25011/cim.v36i1.19400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone Therapy on Cyclophosphamide-induced Urinary Bladder Toxicity in Rats

Abstract: Purpose: is study investigated the e cacy of ozone therapy (OT) in a rat model of cyclophosphamide-induced hemorrhagic cystitis (HC).Methods: Forty Wistar Albino male rats were divided into ve groups: sham, OT, cyclophosphamide (CP), OT+CP and CP+OT. Hemorrhagic cystitis (HC) was induced by intraperitoneal (i.p) administration a single dose of 100 mg/kg CP. OT was performed once daily for three days. e CP+OT group received OT (0.2 mg/kg) i.p 24 h a er CP administration. CP was injected to the OT+CP group the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…There has been considerable interest in researching the role of free radicals in carcinogenesis and the role of antioxidants in the prevention and treatment of cancer and related side effects [ 1 ]. The current study and that of Tasdemir et al [ 29 ] indicated that repeated low doses of O 3 application results in increased antioxidant response. In the current study, O 3 was used in a NMIBC treatment model for the first time.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…There has been considerable interest in researching the role of free radicals in carcinogenesis and the role of antioxidants in the prevention and treatment of cancer and related side effects [ 1 ]. The current study and that of Tasdemir et al [ 29 ] indicated that repeated low doses of O 3 application results in increased antioxidant response. In the current study, O 3 was used in a NMIBC treatment model for the first time.…”
Section: Discussionsupporting
confidence: 74%
“…O 3 has been described as one of the most oxidant agents at high levels (>80 µ g/ml) [ 2 ], but at low levels (20–25 µ g/ml), it is also known to have an antioxidant enhancing effect [ 28 ]. This is known as the paradoxal effect of O 3 [ 29 ]. The biphasic hormetic dose response may be useful for dual pharmacological effects generated by O 3 [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations